1961
DOI: 10.2170/jjphysiol.11.596
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Potentials in Toad's Spinal Motoneurons Due to Muscle Afferent Volleys

Abstract: Although some investigators are dubious of a direct connection between the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1963
1963
1977
1977

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…A number of physiological studies have demonstrated the existence of a segmental monosynaptic reflex in amphibians [Araki, 1960;Fadiga and Brookhart, 1960;F ukami, 1961; H olemans ei a/., 1966; among others]. These studies have suggested that this linkage is principally, if not solely, of an axodendritic character.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of physiological studies have demonstrated the existence of a segmental monosynaptic reflex in amphibians [Araki, 1960;Fadiga and Brookhart, 1960;F ukami, 1961; H olemans ei a/., 1966; among others]. These studies have suggested that this linkage is principally, if not solely, of an axodendritic character.…”
Section: Resultsmentioning
confidence: 99%
“…In this light, the neuroanatomical relationships which have been described in the pres ent investigation may explain certain electrophysiological findings. It has been reported [Araki, 1960;Fadiga and Brookhart, 1960;F ukami, 1961;and H olemans et ai, 1966] that the excitatory postsynaptic poten tials generated directly in amphibian motoneurones by primary afferent fibers only infrequently result in motoneuronal activation. On the other hand, dorsal root stimulation in cat [e.g., Lloyd, 1943] and primates [e.g., P reston and W hitlock, 1960] usually generates monosynaptic ac tivation of motoneurones.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that the same ionic mechanism is responsible for the IPSPs of other central synapses because, like motoneuronal IPSPs, they are readily converted to depolarizing responses by the diffusion of chloride out of an intracellular KC1 microelectrode. The following list gives neurones in which the IPSPs are inverted in this manner: the cells of origin of the dorsal spinocerebellar tract (Curtis et al, 1958); hippocampal pyramidal cells (Kandel et al., 1961; Andersen et id., 1964a); cells of the cuneate nucleus (Andersen et al, 1964b); Purkinje cells of the cerebellum (Eccles et al, 1965); pyramidal cells of the neocortex (Stefanis & Jasper, 1964); toad motoneurones (Fukami, 1961 ); Mauthner cells of fish (Asada, 1963).…”
Section: Mv-mentioning
confidence: 99%
“…There is agreement that inhibitory postsynaptic potentials in frog moto neurons are mediated through oligosynaptic pathways (73,120). The same conclusion is reached about cat motoneurons, where the synaptic delay for excitatory and inhibitory synapses is the same (61).…”
Section: Synapsesmentioning
confidence: 99%